Prolonged orocecal transit time enhances serum bile acids through bacterial overgrowth, contributing factor to gallstone disease - Kaur, Jaspreet; Rana, Satya V; Gupta, Rajesh; Gupta, Vikas; Sharma, Surendra K; Dhawan, Devinder K (Journal of clinical gastroenterology, 2014)
Gallstones (GS) are associated with slow intestinal transit but the effect of altered transit time on physiological changes in gastrointestinal tract among GS patients is poorly understood. To investigate the association of gallstone disease with change in intestinal motility and how motility alters serum bile acid (SBA) levels. A total of 333 subjects were enrolled, of which 183 were GS patients and 150 age-matched and sex-matched controls. Intestinal transit time was assessed by measuring orocecal transit time (OCTT). Breath tests were used to evaluate OCTT and small intestinal bacterial overgrowth (SIBO). Total SBA levels were measured by enzymatic colorimetric assay. A linear regression analysis was performed to look for interrelationship between OCTT and SBA levels. Orocecal transit time was significantly delayed (P<0.001) in GS patients (134.8±30.64 min) compared with controls (85.35±19.81 min). SIBO was observed to be significantly higher (P<0.01) in patients (15%) compared with controls (0.7%). OCTT was further delayed significantly (P<0.01) in GS patients with SIBO (165.6±33.9 min) compared with patients lacking SIBO. Total SBA levels were found to be significantly higher (P<0.05) in GS patients (5.3±2.7 μmol/L) compared with controls (3.7±1.8 μmol/L). SBA levels were also significantly higher (P<0.05) in SIBO-positive GS patients (6.4±2.8 μmol/L) compared with SIBO-negative patients (4.8±2.4 μmol/L). There was positive correlation between OCTT and SBA levels in SIBO-positive patients. The findings indicate that delayed OCTT leads to SIBO and thus enhance SBA levels in etiology underlying GSs.